A physical model for sloping capillary barriers - Rahardjo, Harianto (2011)
A physical capillary barrier model has been developed to study the mechanism and the effectiveness of a capillary barrier for slope stabilization purposes. A sloping two-layer capillary barrier model consisting of a relatively fine soil layer over a relatively coarse soil layer was constructed inside a specially designed apparatus. Simulated rainfalls of different intensities and durations representative of tropical climatic conditions were applied through a rainfall simulator. Various instruments consisting of tensiometers for pore-water pressure measurement, time domain reflectometry (TDR) for water content measurement, magnetic flow meter and electronic weight balances for water balance measurements were used in the experiment. The results obtained from various types of instrumentation were in good agreement. The experimental results show that the performance of the capillary barrier under the influence of a high precipitation rate is primarily governed by the storage capacity of the relatively fine soil of the capillary barrier.